KELAYAKAN FLASH FLIPBOOK PADA SUBMATERI PENCEMARAN LINGKUNGAN KELAS X SMA - Gelagat, Kristianus Kariman; Hardigaluh, Basuki; Candramila, Wolly (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know the water quality and zooplankton diversity in Sungai Ambawang Kalimantan Barat and applied Its result in a flash flipbook as an instructional medium in the sub material of Water Pollution at 10th grade of Senior High School students. Sampling technique used in this research was purposive sampling in which to decide the location of zooplankton sampling, residential, wood industry, and sago vegetation, in Sungai Ambawang. The physical parameter observed were temperature, turbidity, and velocity of water flow. The average of water temperature was 29oC, turbidity in each station in sequence were 23, 22,83, dan 23,83 cm, and velocity of water flow in each station in sequence were 0,16, 0,30, and 0,12 m/s. The chemical parameter were observed are Power of Hydrogen (pH) and Dissolved Oxygen (DO), pH in each station in sequence were 3,36, 3,66 and 3,47, and DO in each station in sequence were 6, 6,10, and 6,4. The Dominance Index of zooplankton in each station in sequence were 0,150, 0,122, and 0,133. The result of dominance index revealed that river in Sungai Ambawang was good. The result was implemented in flash flipbook as an instructional medium in the sub material of Water Pollution. The validity result of flash flipbook by material experts was 3,35 and media experts was 3,50. From the validity result Flash flipbook was valid to be used as an instructional medium in the Sub M֯aterial of Water Pollution at 10th grade of Senior High School students. Keywords: Zooplankton, Dominance Index, Sungai Ambawang, Sub Material of Water Pollution.